THE COMPARATIVE STUDY ANALYSIS LOGICAL FILES RECOVERY AND LOW LEVEL FILES RECOVERY USING DIGITAL FORENSIC METHODS - Rahmat Hidayat; Marza Ihsan Marzuki; Yuliarman Saragih; Ibrahim Ibrahim; Edmund Ucok Armin; Safrian Andromeda; Imam Budi Santoso; Suroyo Suroyo (TEKNOKOM, 2022)
The development of application and network technology is currently so rapid. This technology is widely used as a solution to overcome data inspection problems in the field of Digital Forensics. The importance of Digital Forensics as evidence, especially on computers and mobile devices, is increasing, along with the rapid use of these mobile devices in daily communication. Data and files on computers and smartphones can be deleted intentionally or unintentionally. To recover the data, it is necessary to have Files Recovery. Furthermore, Logical Files Recovery can be made through password encryption, obtained through hack/attack password applications such as Password or even hacked with the "RecoveryMyFile" application. In addition, a search with a file that has a password description can be done. One of the file recovery applications that can be used is the Agent ransack search application, which is more powerful and convenient than Windows Search, which is more complicated if you need to search faster, indexing needs to be done, and restarts. By using Files Recovery analysis, the development of file or data deletion crimes can be overcome with increasingly rapid and advanced information technology, in this case through applications that can be used for file recovery and to restore deleted files.